The EndoBarrier: Duodenal-Jejunal Bypass Liner for Diabetes and Weight Loss - Aruchuna Ruban; Hutan Ashrafian; Julian P. Teare (Gastroenterology Research and Practice)
The rapid rise of obesity and type 2 diabetes poses a global threat to healthcare and is a major cause of mortality and morbidity. Bariatric surgery has revolutionised the treatment of both these conditions but is invasive and associated with an increased risk of complications. The EndoBarrier is a device placed endoscopically in the duodenum, which is designed to mimic the effects of gastric bypass surgery with the aim of inducing weight loss and improving glycaemic control. This review outlines the current clinical evidence of the device, its efficacy, potential mechanisms of action, and utility in clinical practice.